Odzyskane ciało Catherine Sloper. "Plac Waszyngtona" Henry`ego Jamesa w interpretacji Agnieszki Holland = The reclaimed body of Catherine Sloper. Agnieszka Holland`s interpretation of Henry James`s "Washington Square" - Gołębiowska, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to explore the significance of the departures from the novelistic original inAgnieszka Holland`s film adaptation of Henry James`s "Washington Square". The elements omittedas well as those introduced in the film point to a consistent interpretative line adopted by thefilmmakers - to present the main charakter`s development in terms of the awakening of her body.
Keywords: James, Henry (1843-1916); Holland, Agnieszka (1948- ); adaptacja filmowa